Philosophical realism between nature and common sense (part II) - Caro, Mario De (Studia Ecologiae et Bioethicae, 2018)
In a companion article to this one, published in the previous issue of this journal, I discussed the renaissance of philosophical realism, focusing particularly on the different versions of common-sense realism. In this article, I will instead discuss scientific realism and another, intermediate version of realism (which is pluralistic both in ontology and epistemology) that, in my view, incorporates the best elements of common sense realism and scientific realism while avoiding their shortcomings.